Application of Geoportal’s Web-Technologies in GIS, Case Study: Interactive Geology Atlas - Boyarshinov Grigory; Popov Anton; Odintsova Anastasia; Gvozdik Sofia A.; Rybkina Alena; Korolkova Anna (Russian Journal of Earth Sciences)
Abstract: A unique geoinformation service “The Interactive Geology Atlas” has been created and launched based on the data obtained by the Authors during years of research and evaluation of integrated biostratigraphic, paleomagnetic and sedimentological data as well as published references materials. The Interactive Atlas includes geological sections comprehensively studied, described and mapped. Contrary to analogous services, the Atlas covers more territory of Paratethys and time laps and allows to add various content depending on the user requirements. All maps (basemaps) are available for study both individually and joint for comprehensive analysis through the compiling the unified legend to all layers and maps. The combination of different data allows to track how the paleogeographic conditions of the Paratethys territory have evolved and to highlight the main events associated with fluctuations in climate, salinity, etc. Besides being scientifically interesting, the Atlas can become useful in geologic exploration with a view to evaluate the potential areas of mineral resources. For instance, paleogeographic maps are crucial in this regard. FAIR principles have become the reference criteria for improving datasets: Findability, Accessibility, Interoperability, and Reusability.